PENGARUH EARNING PER SHARE (EPS) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERGABUNG DI LQ45 PERIODE 2016-2021 - Cherly Dwi Meivia; Nurul Wahyuni; Noor Hidayati (Smart Business Journal (SBJ), 2024)
Indonesia's economic growth experienced ups and downs. An area that assumes a significant part in building the Indonesian economy is the financial business and the securities exchange. Share prices of banking companies in LQ45 that have experienced significant movement or volatility for the last six years. The identification and verification of the effect that EPS and PER have on stock prices is the focus of this review. This is a quantitative as well as a descriptive type of explanation. The population of this study is all the financial statements of banking companies that are members of LQ45. The financial statements of the LQ45 banking industry for the years 2016 to 2021 were used as the sample size, and objective sampling was used as the sampling method. This study utilized financial reports from the Indonesia Stock Exchange (IDX) as secondary data. a method for compiling reports with information. The data were analyzed using the method of multiple linear regression. The consequences of this study demonstrate that EPS affects stock costs. Stock prices are significantly impacted by PER. Stock prices are greatly influenced by EPS and PER.